Evaluation of Energy Efficient Low Power Listening MAC Protocols in WSN (International Journal of Engineering and Computer Science, 2018)
Medium access control protocols for wireless sensor networks are designed to be energy efficient. An energy efficient MAC protocols are those which reduce idle listening and overhearing .Idle listening may have become the main source of energy waste. To reach average power consumption, most of the time trans-receiver must shut down. This phenomenon allows the nodes to use a lower duty cycle, at no cost of overhead in many cases. Simulation and implementation results show that how fail rate and delay varies in MAC protocols like X-MAC,MX-MAC and SPECK MAC.